The Impact of War on Emergence of Depression and Posttraumatic Stress Disorder on Iranian Veterans of Iran-Iraq War - Mansouri, Aylar (European Journal of Social Science Education and Research, 2019)
Iran has been involved in many wars throughout its ancient history, a vivid example is the Iran-Iraq war. This imposed war was ongoing during September 1980 – August 1988 (Mohsenian, 2008). ).The main goal of this study was to investigate differences depression and PTSD symptoms in veterans who participated in the Iran-Iraq compared to community sample. The objectives of this research were: 1.Comparing depression in soldiers who are PTSD patients and ordinary people. 2. Comparing PTSD symptoms in soldiers and ordinary people. The research hypotheses were formulated according to the defined objectives. The statistical population included the Iran-Iraq war veterans and the ordinary male individuals within the age range of 25-50 residing in Tehran. . The data analysis for present research was down descriptively. The Foundation of Martyrs and Veterans’ Affairs of the city of Tehran permitted the researcher to select the statistical samples through the families of martyrs and veterans in person. The related questionnaires were handed in to the testees in person. The research objectives and nondisclosure of information were explained to the testees prior to distribution of the questionnaire. The data was collected using a PTSD checklist by Weathers, Litz, Herman, Huska, Kean etal (1993) and the Beck depression inventory. The multivariate effect indicates a significant difference between the depression and PTSD in war veterans and ordinary individuals aged 25-50. Depression and PTSD in Iran-Iraq war veterans it was higher compared to ordinary individuals.